2021
DOI: 10.18332/tid/131199
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing and assessing compliance of online vendors to the state of Massachusetts ENDS product sales ban

Abstract: the state (the 15th most populated state in the US). This decision was in direct response to growing concerns associated with the nationwide outbreak of e-cigarette or vaping product use-associated lung ABSTRACT INTRODUCTION Recent reports of lung injury associated with Electronic Nicotine Delivery System (ENDS) products precipitated by increasing vaping prevalence and interest in flavors among adolescents has led to policies that restrict the sale, distribution, and accessibility of ENDS products. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Nali et al [ 59 ] evaluated the compliance of online retailers with the Massachusetts restriction on flavoured ENDS by attempting to purchase flavoured ENDS from 50 online vendors. Of these sites, 80% used some form of age verification, and 76% were non-compliant with the statewide restriction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nali et al [ 59 ] evaluated the compliance of online retailers with the Massachusetts restriction on flavoured ENDS by attempting to purchase flavoured ENDS from 50 online vendors. Of these sites, 80% used some form of age verification, and 76% were non-compliant with the statewide restriction.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with research examining retailers’ compliance with other flavoured tobacco restrictions [ 26 , 66 ]. Compliance studies also suggest additional challenges of regulating the online market, as observed in Massachusetts and India [ 59 61 ].…”
Section: Discussionmentioning
confidence: 99%
“… 35 More recently, several reviews of flavoured e-cigarette bans have reported similar availability of flavoured products among multiple venues and online retailers in San Francisco 36 and Massachusetts. 37 Conflicting data also suggest high compliance by some vendors in San Francisco. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Despite enforcement in 2010, non-cigarette products with explicit and ambiguous descriptors were recognised to be widely available in stores many years after the ban’s implementation 35. More recently, several reviews of flavoured e-cigarette bans have reported similar availability of flavoured products among multiple venues and online retailers in San Francisco36 and Massachusetts 37. Conflicting data also suggest high compliance by some vendors in San Francisco 38…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Several studies have also focused on a measuring the potential impact of a ban in a single retail location or examining the economic and product sales impact on retailers statewide. 26,27 Tobacco control policies that restrict a product's availability are expected to impact sales and revenue due to lowered availability of restricted product primarily at point-of-sale. However, potential unevenness in consequent store closures may unintentionally worsen existing tobacco-related health disparities.…”
Section: Introductionmentioning
confidence: 99%